No Signs of Intracranial Arterial Vasoconstriction in Transient Global Amnesia. Issue 1 (26th February 2014) - Baracchini, Claudio; Farina, Filippo; Ballotta, Enzo; Meneghetti, Giorgio; Manara, Renzo
ABSTRACT BACKGROUND AND PURPOSE The current theories to explain the pathophysiology of transient global amnesia (TGA) involve epilepsy, migraine, and hippocampal ischemia which might be determined by venous congestion or arterial vasoconstriction triggered by Valsalva‐associated maneuvers in susceptible individuals. METHODS Seventy‐five TGA patients [mean age 60.3 ± 8.0 years, 44 (59%) females] and 75 age‐ and gender‐matched controls were enrolled into a case–control study and underwent extracranial and transcranial arterial echo‐color Doppler sonography. RESULTS Intracranial arterial obstructions of the posterior circulation were neither observed in TGA patients nor in controls. There was no significant difference between the two groups with regard to intima–media thickness of the common carotids (.73 ± .07 vs. .72 ± .06), cervical vessel atherosclerosis (13% vs. 15%), >50% intracranial stenosis of the anterior circulation arteries (3% vs. 3%), resistance index values of the vertebral arteries at rest and during Valsalva maneuver (.69 ± .08 vs. .67 ± .09) and pulsatility index values of the major intracranial arteries at rest and during Valsalva maneuver. No difference in all study items was found between patients assessed during or soon after the TGA episode. CONCLUSIONS Extra‐intracranial atherosclerosis does not play a pathogenic role in TGA and no supporting evidence for the arterial vasoconstriction hypothesis of TGA emerged from this study.